ASSESSMENT CRITERIA AS A WAY OF OVERCOMING THE DIFFICULTIES IN COMPLETING SELF-ASSIGNMENTS: A CASE STUDY AT ENU - Tazhitova, gulzhahan; KURMANAYEVA, D. (Pedagogy and Psychology, 2024)
Assessment in academic writing is a crucial element in evaluating master’s students’ comprehension, analytical skills, and ability to communicate ideas effectively, ultimately enhancing their critical thinking and professional abilities. This article focuses on the difficulties master’s students encountered when practicing academic writing and doing self-assignments (such as their thesis or other degree-mandated papers), as well as the strategies they used to overcome those difficulties. The purpose of the study was to investigate appropriate assessment criteria for self-assignments to address the challenges in completing self-assignments. Data were gathered using a survey. The results show that master’s students have had various difficulties in completing their self-assignments. This study raises a few issues to address these students’ particular demands in terms of their academic writing backgrounds and to guarantee their academic success. The authors suggest that the implementation of assessment criteria will facilitate master’s students in completing their self-assignments and succeeding in their degrees. Some approaches are emphasized for the important aspects of the study to help master’s students improve their research abilities as they work in their specific field of study.